Mortality Patterns and Public Health in Hamilton, Canada, 1900–14 - Gagan, Rosemary (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1989)
In recent years a wide-ranging debate has focused on the origins and extent of the decline in mortality rates in Britain in the 18th century and in North America during the closing decades of the 19th century. Some historians suggest that the decrease was tied to a general improvement in living standards and in particular to better nutrition while others point to municipal public health measures carried out by vigilant medical health officers.This paper examines the experience of Hamilton, Ont., during a period of extreme urban and industrial expansion, 1900-14. The evidence, both qualitative and quantitative, suggests that these years were not a ''golden age" of public health: the health of Hamiltonians did not improve, and, in fact, mortality rates increased. Moreover, infants and children of the working class were the most obvious casualties of an inhospitable environment that hurt those least able to exert any degree of control over their circumstances. Public health was not a popular cause in the city, and as a consequence, much of the minimal progress that did occur was either fortuitous or the result of the exertions of one man, Dr James Roberts, the crusading medical health officer.